Perceptions Towards the Use of Drones in Learning Among Mechanical and Manufacturing Engineering Students - Hasnan, Nur Hafizah; Sulaiman, Nor Lisa (Research and Innovation in Technical and Vocational Education and Training, 2024)
In the 4.0 revolution, drone technology is a key technology in the field of automation and robotics. The goal of the National Space Agency in providing active space exposure by 2030, involves the advancement of drone technology in assisting human tasks in various fields. The technology development process takes a long time to achieve this goal. Various factors such as existing understanding, knowledge, skills, and acceptance of drone technology should be studied. Therefore, this study aims to identify the perception of understanding, acceptance, and application of drones among students of the Faculty of Mechanical and Manufacturing Engineering (FKMP) of UTHM. This survey study uses a quantitative approach by distributing a questionnaire to 241 students of the Faculty of Mechanical and Manufacturing Engineering (FKMP) of UTHM to study the perception of understanding of drones, the acceptance of drones in learning, and the application of drones. Data were analyzed using descriptive statistical analysis. Descriptive analysis was conducted by taking the mean score and standard deviation. The results of the study found that the perception of understanding of drones shows a high level due to the widespread use of drones in various fields. The perception of the acceptance of drones in learning shows a high level which also proves the willingness of students to explore this technology more deeply. Meanwhile, the application of drones is at a medium-high level showing mastery of skills or knowledge to be applied to drone technology still needs improvement to realize the 2030 goal of active space exposure. This study suggests that drone-related programs involve the participation of students from other fields to integrate various skills and knowledge in the exploration of drone technology.